An insight into anticancer perspectives of chickpea bioactive compounds - Sabrina Sehar; Roshina Rabail; Seemal Munir; Khunsha Shakeel; Anees Ahmed Khalil; Tabussam Tufail; Muhammad Abid; Kinza Mukhtar; Brera Ghulam Nabi; Gulden Goksen; Rana Muhammad Aadil (Food Chemistry Advances, 2023)
Cancers of the lung, colon, liver, stomach, and breast are common worldwide and have significant fatality rates. Cachexia caused by cancer is the major cause of death in cancer patients, and malnutrition and metabolic illnesses have become more widespread in recent years. To combat these health conditions, proper nutrition is essential. Chickpeas include a variety of bioactive components, including antioxidants, phytochemicals, and bioactive peptides, all of which have preventative and protective health effects. This review summarizes the evidence-based studies on chickpeas’ ability to serve as a valuable source of bioactive chemicals that can help protect against many types of cancer. Chickpeas include secondary metabolites including quercetin and myricetin, as well as phenolic acids and vitamins A, B, and E, which may protect the body from free radicals. Chickpeas have the highest total phenolic content and essential amino acid concentration of any germinated seed. Chickpea storage proteins, such as globulins, glutelins, albumins, and prolamins, are high in protein and can help with cachexia. These proteins contain angiotensin-converting enzyme inhibitory and anti-proliferative capabilities, making them useful in the treatment of a wide range of cancers. As a result, this article provides advice to consumers on improving their eating habits to protect against and fight cancer and may serve as a foundation for future clinical studies.